Machiavelliana : the living Machiavelli in modern mythologies - Grace, Damian. (Value Inquiry Book Series, 2018)
In Machiavelliana Michael Jackson and Damian Grace offer a comprehensive study of the uses and abuses of Niccolò Machiavelli's name in society generally and in academic fields distant from his intellectual origins. It assesses the appropriation of Machiavelli in didactic works in management, social psychology, and primatology, scholarly texts in leaderships studies, as well as novels, plays, commercial enterprises, television dramas, operas, rap music, Mach IV scales, children's books, and more. The book audits, surveys, examines, and evaluates this Machiavelliana against wider claims about Machiavelli. It explains the origins of Machiavelli's reputation and the spread of his fame as the foundation for the many uses and misuses of his name. They conclude by redressing the most persistent distortions of Machiavelli.